2023
DOI: 10.1007/s12311-022-01507-z
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Neurofilament Light Chain and Neurochemistry Deficits in Patients with Spinocerebellar Ataxia Type 3

Abstract: Extensive evidence supports the claim that serum neuro lament light chain (sNfL) can be used as a biomarker for monitoring disease severity in patients with spinocerebellar ataxia type 3 (SCA3). However, little is known about the associations between sNfL levels and neurochemical alterations in SCA3 patients. Serum samples were collected from ATXN3 mutation carriers (n = 20) and normal controls (n = 14). sNfL levels, measured by a single-molecule array, were compared between SCA3 patients and controls. We expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Altered tCho levels have been previously linked to oligodendrocyte disturbances, due to the role of choline in cell membrane synthesis and energy metabolism. 32,37 Patients with SCA3 exhibit decreased cerebellar vermis NAA/Cr ratios, 49 and patients with SCA1 exhibit decreased pons Cho/Cr ratios 35 that are paralleled by mouse models, with rescue of cerebellar tCho levels under ASO treatment. 22 We found a pronounced correlation between brainstem tCho levels and reduction in aggregated high-molecular weight and mutant monomeric ATXN3, suggesting a noteworthy correlation between oligodendrocyte function and mutant protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Altered tCho levels have been previously linked to oligodendrocyte disturbances, due to the role of choline in cell membrane synthesis and energy metabolism. 32,37 Patients with SCA3 exhibit decreased cerebellar vermis NAA/Cr ratios, 49 and patients with SCA1 exhibit decreased pons Cho/Cr ratios 35 that are paralleled by mouse models, with rescue of cerebellar tCho levels under ASO treatment. 22 We found a pronounced correlation between brainstem tCho levels and reduction in aggregated high-molecular weight and mutant monomeric ATXN3, suggesting a noteworthy correlation between oligodendrocyte function and mutant protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the observed correlation between serum NfL and cerebellar neurochemicals in aged homozygous Q84/Q84 mice suggests an association between the magnitude of cellular disturbances and blood NfL. Studies in patients with SCA3 have revealed notable correlations between increased serum NfL levels and neurometabolite abnormalities, specifically decreased cerebellar NAA/Cho and NAA/Cr ratios (Chen et al, 2023). Interestingly, we observed no correlation between NfL and tNAA or myo-Ins, markers of neuronal health and glial contributions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, decreased tNAA has been demonstrated in multiple neurodegenerative diseases ( Adanyeguh et al, 2015 ), including SCA3 ( Miranda et al, 2022 ; Chandrasekaran et al, 2022 ), and is classified as a marker of neuronal and axonal degeneration. A recent study in patients with SCA3 revealed notable correlations between increased serum NfL levels and neurometabolite abnormalities, specifically decreased cerebellar NAA/choline and NAA/creatine ratios, reflective of neuronal degeneration in the cerebellum ( Chen et al, 2023 ). Intriguingly, our study found no correlation between serum NfL and cerebellar tNAA.…”
Section: Discussionmentioning
confidence: 99%